2004
DOI: 10.1007/s10165-004-0325-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticyclic citrullinated peptide antibodies in patients with mixed connective tissue disease

Abstract: The clinical significance of anticyclic citrullinated peptide (CCP) antibodies in patients with mixed connective tissue disease (MCTD) was assessed. Altogether, 86 sera from MCTD patients, 96 from rheumatoid arthritis (RA) patients, 42 from systemic lupus erythematosus (SLE) patients, 23 from systemic sclerosis (SSc) patients, 21 from polymyositis/dermatomyositis (PM/DM) patients, and 17 from those with Sjögren's syndrome (SjS) were tested for anti-CCP antibodies using an enzyme-lined immunosorbent assay. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…The criteria used to select subjects were quite different among the studies; deforming or erosive arthropathy was used in some18,20–22, while others were based on ACR criteria for RA13,19, suggesting that variability in patient selection criteria may be partly responsible for the inconsistent results. Two studies that used deformity or erosion as selection criteria18,22 showed low frequencies (13% and 7%, respectively) of anti-CCP, similar to our present study, whereas others that primarily used erosion20,21 reported a high prevalence (80% and 50%, respectively; Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria used to select subjects were quite different among the studies; deforming or erosive arthropathy was used in some18,20–22, while others were based on ACR criteria for RA13,19, suggesting that variability in patient selection criteria may be partly responsible for the inconsistent results. Two studies that used deformity or erosion as selection criteria18,22 showed low frequencies (13% and 7%, respectively) of anti-CCP, similar to our present study, whereas others that primarily used erosion20,21 reported a high prevalence (80% and 50%, respectively; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, a detailed description of the arthritis seen in these patients was not given16. Conversely, those studies that have described an association of deforming or erosive arthropathy in SLE with anti-CCP positivity did not verify the citrulline dependence of anti-CCP in these patients13,1822. SLE in this subset may have a pathogenesis similar to RA and thus have citrulline-dependent anti-CCP antibodies, whereas anti-CCP in other subsets of SLE may be citrulline-independent.…”
mentioning
confidence: 94%
“…However, while IgM RF concentrations have been found to decrease with treatment (DMARDS with/out infliximab), anti-CCP antibody concentrations do not appear to change [7], limiting the use of anti-CCP as a marker of disease activity and precluding its application as an indicator of response to treatment. There is an increasing evidence that anti-CCP antibodies are also detected in patients with other connective tissue diseases including Sjögren's syndrome, systemic lupus erythematosus, systemic sclerosis, mixed connective tissue disease, and idiopathic inflammatory myositis [23,24].…”
Section: Anti-ccp Antibodymentioning
confidence: 99%
“…The frequencies of anti-CCP and rheumatoid factor (RF) are both *70%; however, anti-CCP is much more specific for RA. Nevertheless, anti-CCP may be positive in up to 10-20% of other rheumatic diseases and associated with chronic arthritis or Jaccoud'stype arthritis in SLE [49]. Anti-CCP in nonrheumatic disease patients is less extensively studied, and one may find unexpected positives in infections, such as in patients with pulmonary tuberculosis [50].…”
Section: Ramentioning
confidence: 98%